A sodium alginate-based nano-pesticide delivery system for enhanced in vitro photostability and insecticidal efficacy of phloxine B. (1st November 2020) - Yin, Yihua; Yang, Mengdan; Xi, Jing; Cai, Weiquan; Yi, Ying; He, Guanghua; Dai, Yue; Zhou, Ting; Jiang, Mengqing
Graphical abstract: Schematics of synthesis and self-assembly of PB-GSA as well as in vitro photostability and esterase/GSH triggered photoactivity of its self-assembly. Highlights: A novel nano-pesticide delivery system was constructed based on conjugates of phloxine B and sodium alginate. The system could effectively inhibit the in vitro photolysis of phloxine B due to aggregation-caused quenching effect. Upon exposure to esterase-6 and/or GSH stimulus, the high photoactivity of system was observed. Compared with free PB, The system showed a higher phototoxicity on Sf9 insect cells. The system will be useful in improvement of insecticidal efficacy of phloxine B. Abstract: To improve in vitro photostability and enhance insecticidal activity, a novel esterase/glutathione (GSH) responsive photoactivated nano-pesticide delivery system was synthesized by conjugation of photoactivated pesticide phloxine B(PB) to sodium alginate (SA) via esterase/GSH sensitive phenolic ester bond followed by ultrasonic dispersion. The system was stable in PBS (pH 7.4) and could protect effectively the conjugated PB from in vitro photodegradation because of aggregation-caused quenching effect, whose maximum photodegradation rate did not exceed 10 % after 270 min illumination. However, upon exposure to esterase-6 or GSH stimulus, high photoactivity was observed due to the destruction of the system and accompanied by PB release. The combined stimulation could trigger more PB release than any single stimulus and thus resulting in a higher photoactivity. Compared with free PB, The system showed a higher phototoxicity on Sf9 insect cells and the in vitro light exposure had little influence on the phototoxicity.